The Destructive Effect of Ingroup Competition on Ingroup Favoritism - Zuo, Youxia; Chen, Bing; Zhao, Yufang (Frontiers in Psychology, 2018)
In-group favoritism has been widely verified in the context of intergroup competition; however, how competition among ingroup members affects ingroup favoritism remains unclear. We hypothesized that competition among ingroup members may disrupt individuals’ ingroup-favoring behavior because of conflicts of interest; we tested this hypothesis in two studies. In Study 1, we manipulated competitive intragroup outcome interdependence (present vs. absent) and the manner in which results were presented (public vs. anonymous). We found that regardless of result presentation, when competitive intragroup outcome interdependence was present, ingroup members did not exhibit ingroup favoritism; when such interdependence was absent, they showed ingroup favoritism. In Study 2, we introduced the manipulation of social identification, and reverified the main result that individuals under competitive intragroup outcome interdependence do not exhibit ingroup favoritism. Even the degree of social identification—a vital factor for intergroup behavior—could not moderate the destructive effect of competitive intragroup outcome interdependence on ingroup favoritism. Together, these findings indicate that ingroup favoritism would indeed be damaged by competition among ingroup members.